Sustainable Synthetic Approaches Involving Thiocyanation and Sulfur-Cyanation: An Update - Gulea, Mihaela; Donnard, Morgan (Current Green Chemistry, 2020)
This review highlights the achievements in the synthesis of organic thiocyanates (OTCs) over the past five years (late 2015 to mid-2019) and is intended as a follow-up on our tutorial review published in Chemical Society Reviews in 2016. The discussion places a special emphasis on sustainable synthetic approaches involving thiocyanation or sulfur-cyanation. The large number of contributions within this short period of time clearly indicates that the chemistry of OTCs provides a growing interest and a rapid evolution.
Keywords: difunctionalization